2015
DOI: 10.1007/978-3-319-07085-8
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling Dynamics in Open Ultracold Bosonic Systems

Abstract: Abstract:This thesis explores the quantum many-body tunneling dynamics of open ultracold bosonic systems with the recently developed multiconfigurational timedependent Hartree for bosons (MCTDHB) method. The capabilities of MCTDHB to provide solutions to the full time-dependent many-body problem are assessed in a benchmark using the analytically solvable harmonic interaction Hamiltonian and a generalization of it with time-dependent both one-and two-body potentials. In a comparison with numerically exact MCTDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 92 publications
(197 reference statements)
0
71
0
Order By: Relevance
“…The analytical ground state wavefunction and energy are used to ensure the convergence of the imaginary time propagation and, as expected, are the same for all methods. The dynamics is initiated at t=0 by quenching instantaneously the strength of the two-body interaction, as performed in [25,26], leading to the evolution of the system under the action of the following Hamiltonian,…”
Section: Application To a Time-dependent System: Dynamics Of Bosons Wmentioning
confidence: 99%
See 1 more Smart Citation
“…The analytical ground state wavefunction and energy are used to ensure the convergence of the imaginary time propagation and, as expected, are the same for all methods. The dynamics is initiated at t=0 by quenching instantaneously the strength of the two-body interaction, as performed in [25,26], leading to the evolution of the system under the action of the following Hamiltonian,…”
Section: Application To a Time-dependent System: Dynamics Of Bosons Wmentioning
confidence: 99%
“…One model uses an inverse-harmonic interaction between the particles and can be solved exactly with a harmonic trapping potential [22], while an other model considers a harmonic interaction potential [23,24]. The latter model has the peculiarity that it can be solved exactly numerically also for time-dependent Hamiltonians with a time-dependent trapping potential or a time-dependent interaction potential for bosons [25,26] and fermions [27].These exact models, unfortunately, do not cover the large variety of interaction or trapping potentials that are encountered in experiments. Nonetheless, they are of primary interest as they provide a unique way to benchmark numerical methods and approximations.…”
mentioning
confidence: 99%
“…We found that the effect appears at larger tilts (α=7.1) for the case of M=4. We therefore speculate that the next-to-nearest neighbor coherence results from a resonance condition involving two-or many-particle correlated tunneling processes [39,62,63]; the lowered energy at the M= 4-level of MCTDHB (footnote 5) seems to cause the resonance condition to be fulfilled at a different tilt.…”
Section: First-order Correlationmentioning
confidence: 93%
“…are a complete basis set of N-body Hilbert space for M  ¥, the variational principle [45] guarantees that the solutions of the time-dependent manybody problem provided by the MCTDHB method gradually improve towards exactness when the number of considered creation operators M in the ansatz, equation (5), is increased [36,39]. To derive the MCTDHB equations, the time-dependent variational principle [45] is employed to determine the time-evolution of the expansion coefficients C t [37,38].…”
Section: Method: the Multiconfigurational Time-dependent Hartree Methmentioning
confidence: 99%
See 1 more Smart Citation